Adoption of Information Technology: Computer Application among Malaysian Civil Service Employees in Selected Agricultural Organisations - Ithnin, Yazid (2000)
This study investigates factors that influence adoption of computer usage in agricultural organisations. Rogers' (1995) rate of adoption of innovations model was used as the research framework. The study focused on whether or not the adoption of innovation factors adapted from the model could explain and predict the computer usage adoption among employees of agricultural organisations in Malaysian civil service. The dependent variable was adoption of computer usage. The five independent variables were perceived attributes of computerisation, types of adoption-decision, communication channels, nature of social system and promotional efforts. The study employed the survey research technique. Sampling was done by using the multi-stage random sampling technique in selecting 219 employees from six (FAMA, MARDI, DOA, LPP, BPM and DVS) out of 12 organisations. Respondents' usage of ten computer applications namely Wordprocessing, Spreadsheet, Data Base, graphics, Presentation, Desktop Publishing, Statistical Data Processing, E-maiL Internet and other specific organisational applications, were studied. Data were collected by mailed self-administered questionnaire. Both descriptive and inferential statistics were utilised in data analyses. The study should that computer usage adoption level among all employee categories and in all organisations was low. The highest adoption level was in Wordprocessing and the least in organisational application specific to that organisation. Adoption pattern did not differ much among organisations. In terms of categories, 1.8% of respondents could be categorised as innovators, 25.1% early adopters, 48.4% early majority, 24.7% late majority and no laggards. Adoption behaviours were not significantly different in terms of organisations. The wider the coverage of promotional effort, the higher would be the adoption.